Transformed Health Ecosystems—Challenges for Security, Privacy, and Trust - Ruotsalainen, Pekka; Blobel, Bernd (Frontiers in Medicine, 2022)
A transformed health ecosystem is a multi-stakeholder coalition that collects stores and shares personal health information (PHI) for different purposes such as for personalized care, prevention, health prediction, precise medicine, personal health management and public health purposes. Those services are big data driven and a lot PHI is needed not only from the care and treatments, but also from person’s normal life. Collecting, processing, sharing and storing a huge amount of sensitive PHI in the ecosystem causes many security, privacy and trust challenges to be solved. The authors have studied those challenges from different perspectives using existing literature and found that current security and privacy solutions are insufficient, and for the user it is difficult to know whom and how much to trust. The widely used notice-and-choice privacy model as well as belief and perception based trust approaches do not work in digital health ecosystems. The authors state that it is necessary to redefine the way privacy and trust are understood in health and develop new legislation to support new privacy and approaches and force the stakeholders of the health ecosystem to make openly available their privacy and trust practices and features of their information systems. The authors have also presented some candidate solutions for security, privacy and trust in future heath ecosystems.